In-building direct wastewater heat recovery solutions for enhancing thermal efficiency in domestic hot water systems - Balan Mircea; Sandu Mihnea; Bode Florin (E3S Web of Conferences)
Enhancing energy efficiency in buildings is necessary for reducing environmental impact and operational costs, with domestic hot water (DHW) systems accounting for a significant portion of residential energy consumption. This paper provides a comprehensive overview of in-building direct wastewater heat recovery (WHR) systems as a means to improve thermal efficiency in DHW systems. Various direct WHR technologies are explored, focusing on vertical and horizontal heat exchangers, detailing their design, operation, and efficiency. The study analyses factors influencing the performance of these systems, including heat exchanger design, temperature differentials, flow rates, and maintenance requirements. Case studies are presented to demonstrate the practical applications and energy savings potential of WHR systems in residential and commercial buildings. Despite the clear benefits, challenges such as installation complexity, maintenance needs, usage patterns, and initial costs hinder widespread adoption. Retrofitting existing buildings poses significant hurdles due to space constraints and plumbing modifications, while maintenance is essential to prevent efficiency losses from fouling. The effectiveness of WHR systems is also influenced by the synchronization of hot water usage and wastewater production, which can be intermittent in residential settings. Economic considerations, particularly the upfront investment, can deter stakeholders despite favourable long-term returns.